Tearing down the statues, building up the values. Discrepancy between built and lived environment - Kohoutová, Aneta (Ordem dos Arquitectos Secção Regional Norte, 2022)
In my paper I reflect on discrepancy between built and lived environment, as introduced by Hannah Arendt, in her terms the public realm and space of appereance. According to that I will ask what values and emotions public spaces, namely in this paper, the monuments and public art placed in the shared areas, evoke. My study question could be outlined as follows: What role do monuments and public art play in our lives and how do they shape and influence our identities and the ways we perceive the world? In my presentation I will work with the thoughts of Hannah Arendt, Judith Butler and Sandra Shapshay who promotes an aesthetic category called “monumental” in which she finds a link between the political and the aesthetic function of public art.
Sochy versus hodnoty. Propast mezi žitým a materiálním prostorem
Keywords: statues; public spaces; built environment; lived environment; sochy; hodnoty; žitý prostor; materiální prostor